DEVASTAÇÃO E TRÁFICO DE MADEIRA NO LITORAL DO PARANÁ PROVINCIAL (Revista de História Regional, 2007)
This article points out authorities concern about Atlantic Forest devasta-tion in littoral of Paraná, in the last half of the 19th century. In the authorities speech the illegal trade of the wood turns out as being an activity that involved several local inhabitants of sea coast.